Efficacy and quality‐of‐life improvements with fremanezumab treatment in patients with difficult‐to‐treat migraine with associated neurological dysfunction. (29th March 2022) - Lampl, Christian; Rapoport, Alan M.; Cohen, Joshua M.; Barash, Steve; Ramirez Campos, Verena; Seminerio, Michael J.; Ning, Xiaoping; Silberstein, Stephen D.
Abstract: Background and purpose: Fremanezumab, a fully humanized monoclonal antibody (IgG2Δa) that selectively targets calcitonin‐gene‐related peptide, has demonstrated efficacy as a preventive treatment for adults with episodic migraine or chronic migraine and inadequate response to two to four prior preventive treatment classes in the phase 3b FOCUS study. In this post hoc analysis, efficacy and effects on quality‐of‐life outcomes for fremanezumab were evaluated in subgroups of patients with and without aura or similar neurological symptoms, here referred to as migraine with or without associated neurological dysfunction. Methods: In the FOCUS study, 838 patients were randomized (1:1:1) to quarterly fremanezumab, monthly fremanezumab or matched placebo for 12 weeks of double‐blind treatment. For this post hoc analysis, subgroups of patients with migraine with and without associated neurological dysfunction at baseline were identified based on patient response to questions about symptoms. Results: In patients with migraine with associated neurological dysfunction at baseline, fremanezumab significantly reduced monthly average days with neurological symptoms (quarterly, −1.7 days; monthly, −1.8 days) compared to placebo (−0.5 days; both p  ≤ 0.01). In comparison with placebo, both dosing regimens of fremanezumab yielded greater reductions in monthly migraine days over 12 weeks ( p  < 0.0001) and improvements in Headache Impact Test 6 and Migraine‐Specific Quality of Life scores over the last 4 weeks ( p  < 0.05), regardless of neurological dysfunction at baseline. Conclusions: Fremanezumab reduced days with neurological symptoms, effectively prevented migraine, and improved quality of life in patients with migraine with associated neurological dysfunction, including those with previous inadequate response to two to four migraine preventive medication classes. Abstract : Reductions in days with neurological symptoms are shown in patients with migraine with associated neurological dysfunction. Migraine with aura or similar neurological symptoms, here referred to as migraine with associated neurological dysfunction, may be more severe and harder to treat effectively. In this post hoc analysis of the phase 3b FOCUS study, fremanezumab significantly reduced days with neurological symptoms versus placebo in patients with migraine with associated neurological dysfunction; fremanezumab also reduced monthly migraine days and disability and improved health‐related quality of life in patients with migraine with and without associated neurological dysfunction.